2000
DOI: 10.1046/j.1365-2427.2000.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Structuring features of lake districts: landscape controls on lake chemical responses to drought

Abstract: 1. Within a lake district of relatively homogeneous geomorphology, the responses of lakes to climate are influenced by the complexity of the hydrogeologic setting, position in the landscape, and lake‐specific biological and physical features. We examined lake chemical responses to drought in surface water‐ and groundwater‐dominated districts to address two general questions. (1) Are spatial patterns in chemical dynamics among lakes uniform and synchronous within a lake district, suggesting broad geomorphic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 48 publications
1
109
3
Order By: Relevance
“…7). We attribute this pattern to landscape differences in lake sensitivity to climate change or land use (cf., Webster et al 2000), rather than urbanization, because both Pasqua and Echo Lakes receive sewage, yet exhibit rates of community change similar to those seen in Buffalo Pound Lake.…”
Section: Landscape Patterns Of Invertebrate Community Change-mentioning
confidence: 96%
“…7). We attribute this pattern to landscape differences in lake sensitivity to climate change or land use (cf., Webster et al 2000), rather than urbanization, because both Pasqua and Echo Lakes receive sewage, yet exhibit rates of community change similar to those seen in Buffalo Pound Lake.…”
Section: Landscape Patterns Of Invertebrate Community Change-mentioning
confidence: 96%
“…Each off-diagonal value in this matrix represents the strength of the relationship between the temporal trajectories of chlorophyll a. Longitudinal gradient of nutrient and NVSS from the mouth to the headwater were tested by the regression analysis of concentrations and distance from the mouth. In order to characterize spatial heterogeneity in environmental characteristics, we calculated the relative difference indices (D x ) of environmental variable (DIN, DIP and NVSS) between sites as follow (modified from BAINES et al, 2000;FÖLSTER et al, 2005):…”
Section: Wwwrevhydrocommentioning
confidence: 99%
“…GEORGE et al (2000) examined the extent to which year-to-year variations in the physical, chemical and biological characteristics of five lakes varied synchronously over a 30 ~ 40 year period. WEBSTER (2000) found that chlorophyll a, which are influenced by in-lake processes, were less synchronous. However, phytoplankton populations respond so rapidly and sensitively to their environment that conventional sampling methods fail to obtain more subtle and interesting aspects of the controlling mechanisms of phytoplankton growth.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations